2006
DOI: 10.1074/jbc.m603354200
|View full text |Cite
|
Sign up to set email alerts
|

Of Two Cytosolic Aconitases Expressed in Drosophila, Only One Functions as an Iron-regulatory Protein

Abstract: In mammalian cells, iron homeostasis is largely regulated by post-transcriptional control of gene expression through the binding of iron-regulatory proteins (IRP1 and IRP2) to iron-responsive elements (IREs) contained in the untranslated regions of target mRNAs. IRP2 is the dominant iron sensor in mammalian cells under normoxia, but IRP1 is the more ancient protein in evolutionary terms and has an additional function as a cytosolic aconitase. The Caenorhabditis elegans genome does not contain an IRP2 homolog o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
46
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 57 publications
1
46
0
Order By: Relevance
“…9). It is notable that the expression of each mRNA encoding Bach1 (Igarashi and Sun 2006), HRI (Chen 2007) or IRP2 (Lind et al 2006) is restricted in higher eukaryotes. While CP motifs in the presequence of ALAS are conserved throughout yeast to human except some higher plants, there is no evidence that heme inhibits mitochondrial transport of yeast ALAS precursor either in vivo or in vitro (Duncan et al 1999).…”
Section: Resultsmentioning
confidence: 99%
“…9). It is notable that the expression of each mRNA encoding Bach1 (Igarashi and Sun 2006), HRI (Chen 2007) or IRP2 (Lind et al 2006) is restricted in higher eukaryotes. While CP motifs in the presequence of ALAS are conserved throughout yeast to human except some higher plants, there is no evidence that heme inhibits mitochondrial transport of yeast ALAS precursor either in vivo or in vitro (Duncan et al 1999).…”
Section: Resultsmentioning
confidence: 99%
“…Intron/exon donor and acceptor splice sites flank the GFP sequence on the P element; consequently, all Fer1HCH G188 mRNA types (IRE 1/À) are predicted to contain the GFP exon, which should encode GFP in frame with the Fer1HCH protein ( Figure 2D). Therefore, post-transcriptional regulation of GFP-Fer1HCH mediated by the IRP-1A (Lind et al 2006) would remain unaffected by the GFP exon. GFP is inserted two amino acids downstream of the predicted cleavage site for the Fer1HCH signal peptide (Charlesworth et al 1997), which is encoded from the second exon of the gene ( Figure 2D).…”
Section: G188mentioning
confidence: 99%
“…In contrast, no IRE is present in Fer2LCH mRNA . IRP homologs are expressed in the fly (Muckenthaler et al 1998), and one homolog (IRP-1A) has been shown to bind to IREs from both Drosophila and mammals (Lind et al 2006).…”
mentioning
confidence: 99%
“…As a consequence, some aspects of systemic iron homeostasis, defined as all movement of iron in the organism, and regulatory mechanisms that control this movement maintaining an overall stable condition (Hentze et al, 2004;Nichol et al, 2002), may differ between invertebrates and vertebrates. Nevertheless, key proteins involved in iron regulation have conserved functions as exemplified by the ferritins Missirlis et al, 2007;Pham and Winzerling, 2010), the iron regulatory proteins (Lind et al, 2006) and the transferrins Tiklová et al, 2010). We became interested in the DMT1 homologue in Drosophila melanogaster, encoded by the Mvl gene, originally identified in a mutagenesis screen designed to identify genes affecting taste behaviour in flies (Rodrigues et al, 1995).…”
Section: Introductionmentioning
confidence: 99%